Hubungan antara Perilaku Hygiene Genetalia dengan Kejadian Keputihan Patologis - Eliza Budi Purnasari (Universitas Airlangga, 2018)
Leucorhea is vaginal fluid, sometimes white or gray, can also colored yellow and green, smelling bad and foaming. Leucorhea is a frequent symptom experienced by most women. In Indonesia, about 75% of women had experienced on suffering leucorhea. Leucorhea is a common symptom of almost all reproductive health problem. In Indonesia, the risky age on suffering reproductive infections generally are still undergoing education in schools, so that we decide to conduct our research in senior high school which is SMP Negeri 3 Depok, based on the highest number of teenagers, in Depok, Sleman. The study was conducted to determine the relationship between genetalia’s hygiene behavior towards pathological leucorhea on 7th grade students of SMP Negeri 3 Depok year by 2014. The type of research is an analytic observational with cross sectional aproach. The location is in SMP Negeri 3 Depok on May 9th 2014, with 7th grade students having menstruation record, have not suffered any reproductive health problem and not in stress condition as the subject, 53 in total. We use questionnaire as the instrument. The analysis use univariat and bivariat analysis. The result shows that most respondents had non-hygienic behavior (66.04%) and experienced phatological leucorhea (75.58%). Furthermore, there were 82.9% of respondents with non-hygienic behavior and 55.6% of subjects with hygienic behavior suffered pathological leucorhea. Therefore, given that subjects with genetalia’s hygiene behavior that is not hygienic to have a 1.5 times greater risk for experiencing pathological leucorhea compared with those in hygienic behavior. Chi-square value 4.5583, p value 0.03276, and PR 1.491.